XND1 Regulates Secondary Wall Deposition in Xylem Vessels through the Inhibition of VND Functions. (3rd November 2020) - Zhong, Ruiqin; Kandasamy, Muthugapatti K; Ye, Zheng-Hua
: Secondary wall deposition in xylem vessels is activated by Vascular-Related NAC Domain proteins (VNDs) that belong to a group of secondary wall NAC (SWN) transcription factors. By contrast, Xylem NAC Domain1 (XND1) negatively regulates secondary wall deposition in xylem vessels when overexpressed. The mechanism by which XND1 exerts its functions remains elusive. We employed the promoter of the fiber-specific Secondary Wall-Associated NAC Domain1 ( SND1 ) gene to ectopically express XND1 in fiber cells to investigate its mechanism of action on secondary wall deposition. Ectopic expression of XND1 in fiber cells severely diminished their secondary wall deposition and drastically reduced the expression of SWN-regulated downstream transcription factors and secondary wall biosynthetic genes but not that of the SWN genes themselves. Transactivation analyses revealed that XND1 specifically inhibited SWN-activated expression of these downstream genes but not their MYB46-activated expression. Both the NAC domain and the C-terminus of XND1 were required for its inhibitory function and its NAC domain interacted with the DNA-binding domains of SWNs. XND1 was shown to be localized in the cytoplasm and the nucleus and its co-expression with VND6 resulted in the cytoplasmic sequestration of VND6. Furthermore, the C-terminus of XND1 was indispensable for the XND1-mediated cytoplasmic retention of VND6 and its fusion to VND6 was able to direct VND6 to the cytoplasm and render it unable to activate the gene expression. Since the XND1 gene is specifically expressed in xylem cells, these results indicate that XND1 acts through inhibiting VND functions to negatively regulate secondary wall deposition in xylem vessels.